'Her hair over her arms and her arms full of flowers': Love and Unknowing in Alina Marazzi's Un'ora sola ti vorrei (For One More Hour with You) (2002). Issue 1 (March 2015) - Wilson, Emma
<x xml:space="preserve">Abstract</x> In her first documentary film, For One More Hour with You (2002), Alina Marazzi explores ways of using cinema, and in particular carefully edited found footage, to attend to sensory presence, to girlhood, to female sexuality, to sensuality and love. Marazzi's work is sensitive to ways in which cinema may conjure another individual as sensate and animate, as affectively and erotically present, as touched, elated and damaged. Yet her work is also finely attuned to protection and to ethical delicacy, forging a responsive sensibility, reminding us of all that we also don't know of each other. Her focus on her mother Liseli Hoepli Marazzi, on her loves, on the moves from girlhood into more charged erotic and affective experience, is part of a broader feminist agenda. Marazzi's work encourages viewers to feel, to attend to sensation, whilst remaining uncertain of what is seen or heard.